Tren Kajian Komunikasi Islam di Indonesia - Imamah, Fardan Mahmudatul (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
This article discusses trends in the study of da'wah, specifically communication and Islamic broadcasting, which are discussed in scientific journals. This study uses a literature study approach to 11 journals published by the Islamic Communication and Broadcast Study Program in Indonesia. 581 articles were determined to be the subject of research. Each article is mapped based on (1) the theme and subject of the study, (2) the data collection method, (3) the approach or theory used, (4) the reference source used. The results of the data analysis showed that most of the articles with the theme 'Da'wah' from various platforms of various research subjects. This study opens a new paradigm in communication in general. This is marked by the enrichment of communication and broadcast theories through research in da'wah studies.